Shelter Worker's Experiences and Perceptions of Capacity for Care (C4C). Issue 1 (2nd January 2023) - Hobson, Samantha; Bateman, Shane; Coe, Jason B.; Oblak, Michelle L.
ABSTRACT: Capacity for Care (C4C) is a shelter management strategy which utilizes managed intake to optimize in-shelter populations based on housing capacity and available resources. The purpose of this study was to 1) understand staff experiences using managed intake, 2) explore staff perceptions of how the C4C model has been regarded by other staff at their facility, and 3) explore the response of community members who are attempting to relinquish their cats, as perceived by the staff who are communicating with cat owners and scheduling relinquishment. Participants recruited from shelters who practiced C4C participated in a semi-structured interview and completed a written survey to share their experiences and perceptions of C4C. Based on the perceptions of the participants, evidence suggests the waitlist may decrease the admission of owned cats to the shelter as a result of advising cat owners about alternatives to relinquishment. The findings suggest that more research is needed to understand the potential impacts of managed intake, as an element of C4C, on the welfare of cats in the community who are waiting to be admitted to a shelter.